Textual Features of the Epic “Hayrat-ul abror”: Fitur Tekstual dari Epik “Hayrat-ul abror” - Murodova Gulchehra Azamat (Academia Open, 2022)
A lot of work has been done to study and publish the works of Alisher Navoi, a great artist. In addition, the poet's epic "Hayrat ul abror" has been published several times on the basis of manuscripts and lithographs. The article introduces the traditional introductory chapters of Alisher Navoi's epic "Hayratul abror", ie the 6th volume of the XV volume of the collection, the 7th volume of the XX volume of the Complete Works, the 6th volume of the X volume of the Complete Works. Volumes were compared with the scientific-critical text compiled by the textologist P. Shamsiyev, and the differences in publication were identified